(untitled) (Research, Society and Development, 2021)
The aim of the study was to investigate the available literature, papers that present the correlation of congenital hypertrichosis with craniofacial changes and neurological and neuromotor involvement in pediatric and adult patients. The search was carried out in the Online Mendelian Inheritance in Man (OMIM), Protein and Pubmed-NCBI databases, and no limiting period was established as to the date of publication. The descriptors used in English were "Hypertrichosis", "Neurodevelopmental Disorders" and "Craniofacial Abnormalities". Only papers on syndromes that had an association between hypertrichosis and craniofacial, neurological, and neuromotor abnormalities were included. Those that did not fit these criteria were excluded, such as papers addressing only malformations, congenital abnormalities, and when isolated Hirsutism was mentioned. The OMIM search resulted in 148 conditions that mentioned hypertrichosis, of these only 27 met the inclusion criteria. It is noted that characteristics of general and head and neck alterations were commonly found, among them: Hypertrichosis, intellectual disability, mental retardation, highly arched palate, gingival hyperplasia, and dysmorphic ears. Therefore, it is of utmost importance that the dentist be attentive, know how to identify and document somatic and facial alterations, in order to help in the identification and confirmation of syndromes, as well as to provide a more accurate diagnosis and better outcome for the treatment of the alterations in the oral cavity.